Elucidating the tight-binding mechanism of two oral anticoagulants to factor Xa by using induced-fit docking and molecular dynamics simulation. Issue 2 (22nd January 2020) - Du, Qingqing; Qian, Yan; Yao, Xiaojun; Xue, Weiwei
Abstract: Communicated by Ramaswamy H. Sarma